2021
DOI: 10.3389/fpsyg.2021.586983
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Terroir and the Premium Coffee Experience

Abstract: With its origin-centric value proposition, the specialty coffee industry seeks to educate consumers about the value of the origin of coffee and how the relationship with farmers ensures quality and makes coffee a premium product. While the industry has widely used stories and visual cues to communicate this added value, research studying whether and how these efforts influence consumers' experiences is scarce. Through three experiments, we explored the effect of images that evoke the terroir of coffee on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 142 publications
0
11
0
1
Order By: Relevance
“…In previous research the smell of coffee has also unexpectedly been found more congruent to certain visual stimuli as intended (cf. Barbosa Escobar et al, 2021 ). Thorough pre-testing of stimuli before conducting further elaborate experiments is therefore advisable.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research the smell of coffee has also unexpectedly been found more congruent to certain visual stimuli as intended (cf. Barbosa Escobar et al, 2021 ). Thorough pre-testing of stimuli before conducting further elaborate experiments is therefore advisable.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“… Loureiro et al, 2021 ) and the “post-purchase stage” which concerns consumption of and engagement with the product/brand and after sales service (cf. Liu et al, 2019 ; Barbosa Escobar et al, 2021 ). Also noteworthy is the conceptual framework provided by Hollebeek et al (2020) on the role of VR in marketing throughout the customer journey, where they distinguish between the pre-, the intra- and the post-VR experience and provide a useful classification of VR archetypes, formats and content features, calling for more research in this domain.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The majority of XR eating research has focused, so far, on real scenarios obeying the laws of physics (quadrant 1). Using VR, for example, studies have explored drinking coffee while immersed in a coffee farm (Barbosa Escobar et al, 2021). Using stereoscopic AR interfaces, other studies have investigated altering the luminance distribution of a slice of cake and changing the apparent size of a cookie .…”
Section: Impossible Xr Eating Experiencesmentioning
confidence: 99%
“…The majority of XR eating research has focused, so far, on real scenarios obeying the laws of physics (quadrant 1). Using VR, for example, studies have explored drinking coffee while immersed in a coffee farm (Barbosa Escobar et al, 2021). Using stereoscopic AR interfaces, other studies have investigated altering the luminance distribution of a slice of cake (Ueda et al, 2020) and changing the apparent size of a cookie (Narumi et al, 2012).…”
Section: Impossible Xr Eating Experiencesmentioning
confidence: 99%